2018
DOI: 10.1016/j.jcmgh.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Promotes Parietal Cell Atrophy by Inducing Apoptosis

Abstract: Background & AimsAtrophic gastritis caused by chronic inflammation in the gastric mucosa leads to the loss of gastric glandular cells, including acid-secreting parietal cells. Parietal cell atrophy in a setting of chronic inflammation induces spasmolytic polypeptide expressing metaplasia, a critical step in gastric carcinogenesis. However, the mechanisms by which inflammation causes parietal cell atrophy and spasmolytic polypeptide expressing metaplasia are not well defined. We investigated the role of interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 47 publications
(59 reference statements)
0
46
0
Order By: Relevance
“…This is a critical observation, as IFN‐γ regulates many cellular behaviors and it was, prior to these studies, entirely plausible that the effects of IFN‐γ on gastric epithelium could be an indirect effect caused by downstream products of IFN‐γ signaling. Another feature of our study is that we show that atrophy and metaplasia in TxA23 mice, which eventually progress to marked cancer‐like dysplasia , depend nearly entirely on IFN‐γ, as TxA23 × Ifng −/− mice have inflammation but minimal other pathology, even at advanced age (5–7 months) for this model. We specifically determine that it is IFN‐γ within the supernatants from draining‐lymphocytes of wild‐type mice that is elevated in TxA23 mice and lost in Ifng −/− mice, with other cytokines not being significantly affected.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…This is a critical observation, as IFN‐γ regulates many cellular behaviors and it was, prior to these studies, entirely plausible that the effects of IFN‐γ on gastric epithelium could be an indirect effect caused by downstream products of IFN‐γ signaling. Another feature of our study is that we show that atrophy and metaplasia in TxA23 mice, which eventually progress to marked cancer‐like dysplasia , depend nearly entirely on IFN‐γ, as TxA23 × Ifng −/− mice have inflammation but minimal other pathology, even at advanced age (5–7 months) for this model. We specifically determine that it is IFN‐γ within the supernatants from draining‐lymphocytes of wild‐type mice that is elevated in TxA23 mice and lost in Ifng −/− mice, with other cytokines not being significantly affected.…”
Section: Discussionmentioning
confidence: 54%
“…The finding that the predominant cytokine produced during both Helicobacter infection and autoimmune gastritis is capable of directly inducing epithelial cell death should advance our understanding of the pathogenesis of inflammation-induced gastric carcinogenesis. We have previously shown that another major component of the inflammatory milieu, IL-17A, can directly induce parietal cell atrophy via apoptosis [8]. It should be noted that data from both that study and this current one indicate that IFN-γ is roughly 100 times more concentrated and 10 times more potent at inducing cell death compared with IL-17A alone, and it is reasonable to hypothesize that there is a strong potential for synergy between these two arms of the immune response given that they have little overlap in their signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations